Modification of the conditions of the authorisation of BioPlus® 2B (Bacillus licheniformis DSM 5749 and Bacillus subtilis DSM 5750) for turkeys for fattening. (14th June 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the modification of the terms of the authorisation of BioPlus ® 2B ( Bacillus licheniformis DSM 5749 and Bacillus subtilis DSM 5750) in feeds for turkeys for fattening to allow the simultaneous use with a battery of permitted coccidiostats (diclazuril, halofuginone, monensin sodium, robenidine hydrochloride, maduramicin ammonium, lasalocid sodium) and with the preservative formic acid. The proposed modification in the conditions of the authorisation would not modify the conclusions previously drawn regarding the safety of the additive. The additive is safe for the target species, consumers and the environment. The additive should be considered a potential respiratory sensitiser, but the Panel could not conclude on the irritancy of the additive to skin and eyes or its dermal sensitisation. Conclusions previously drawn by the FEEDAP Panel on the compatibility of the additive for chickens for fattening apply to the current application provided that the maximum authorised concentration of the coccidiostats semduramycin, maduramicin ammonium, lasalocid sodium and the preservative formic acid for turkeys for fattening (when maximum authorised concentrations exist), are equal or lower than those for chickens for fattening. Considering the data submitted, the FEEDAP Panel concludes that BioPlus ® 2B ( B . licheniformis DSM 5749 and B . subtilis DSM 5750) is compatible with diclazuril and monensin sodium. Based on the data provided, no conclusion can be drawn for robenidine hydrochloride. In the absence of data, no conclusion can be drawn for halofuginone.